2017
DOI: 10.7554/elife.26402
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary changes in transcription factor coding sequence quantitatively alter sensory organ development and function

Abstract: Animals are characterized by a set of highly conserved developmental regulators. Changes in the cis-regulatory elements of these regulators are thought to constitute the major driver of morphological evolution. However, the role of coding sequence evolution remains unresolved. To address this question, we used the Atonal family of proneural transcription factors as a model. Drosophila atonal coding sequence was endogenously replaced with that of atonal homologues (ATHs) at key phylogenetic positions, non-ATH p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…Blocking autoregulation in this way is an effective means of permanently extinguishing gene expression and might be exploited by Notch signaling in many situations (Baker, 2004). In addition, there is increasing evidence that Notch signaling affects proneural protein stability, which would also negatively impact autoregulation (Kiparaki et al, 2015;Weinberger et al, 2017).…”
Section: Drosophila Atonal As a Platform For Understanding Proneural mentioning
confidence: 99%
See 2 more Smart Citations
“…Blocking autoregulation in this way is an effective means of permanently extinguishing gene expression and might be exploited by Notch signaling in many situations (Baker, 2004). In addition, there is increasing evidence that Notch signaling affects proneural protein stability, which would also negatively impact autoregulation (Kiparaki et al, 2015;Weinberger et al, 2017).…”
Section: Drosophila Atonal As a Platform For Understanding Proneural mentioning
confidence: 99%
“…In principle, the origins of functional distinctions between AS-C genes could be addressed in an experiment that tests whether the single homolog of the proneural AS-C genes from honey bees, wasps or mosquitoes could rescue any or all of the Drosophila AS-C genes. The AS-C structure would make this difficult, but a recent study has made use of gene knock-in methods to replace the ato coding region at the endogenous Drosophila locus with sequences encoding other proneural proteins, an assay that should test the functional attributes of various proteins precisely (Table 1) (Weinberger et al, 2017). These studies showed that Amos is almost indistinguishable from its paralog Ato in terms of function when expressed from the ato locus, whereas previous transgenic assays had suggested distinctions between these proteins (Maung and Jarman, 2007;Weinberger et al, 2017).…”
Section: Box 1 Gene Initiation and Maintenance Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maung and Jarman showed that amos is capable to rescue eye development independent of ato 54 . Weinberger et al showed that the coding sequence of amos , when used to replace the coding sequence of ato , is sufficient to produce a fully functional Drosophila ear, the performance of which is statistically identical to the native, ato -induced organ with respect to all quantitative parameters also used in this study 55 . While amos was found to be expressed in adult JOs, no such expression was found for ato .…”
Section: Discussionmentioning
confidence: 60%
“…In cases where the gene of interest carries a single exon, the fly exon in the genomic rescue constructs can be replaced by wild type and variant-containing human exon to assess/compare the ability of these constructs to rescue mutants (Figure 2c′) [63]. For example, the functional impact of a rare TM2D3 human variant that was predicted to be non-pathogenic was identified in association with late onset AD susceptibility [64].…”
Section: Introductionmentioning
confidence: 99%